КРИСТАЛЛОХИМИЧЕСКИЕ ФОРМУЛЫ И ОПРЕДЕЛЕНИЕ ВИДОВОЙ ПРИНАДЛЕЖНОСТИ МИНЕРАЛОВ ГРУППЫ ТУРМАЛИНА - Золотарёв А.А.; Франк-Каменецкая О.В.; Рождественская И.В. (My University, 2006)
Complicated chemical compositions of tourmalines and wide variety of schemes realized in their isomorphism cause significant difficulties for recalculating the chemical analysis data into a crystal-chemical formula. In every case the calculated formula becomes no more than a result of an author's interpretation, and, consequently, any formula is a far or close approach to the reality. The paper discusses possibilities of different ways to represent composition of the tourmaline group minerals. Special attention is given to conditionalities, contradictions and mistakes in drawing the crystal-chemical formulas, and emerging out problems to define, using the obtained formula, the belonging of the mineral to a certain mineral species of the tourmaline group.
Keywords: 549.0